Lateral Fluid Percussion Injury Impairs Hippocampal Synaptic Soluble N-Ethylmaleimide Sensitive Factor Attachment Protein Receptor Complex Formation - Carlson, Shaun W.; Henchir, Jeremy; Dixon, C. Edward (Frontiers in Neurology, 2017)
Traumatic brain injury (TBI) and the activation of secondary injury mechanisms have been linked to impaired cognitive function, which, as observed in TBI patients and animal models, can persist for months and years following the initial injury. Impairments in neurotransmission have been well documented in experimental models of TBI, but the mechanisms underlying this dysfunction are poorly understood. Formation of the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex facilitates vesicular docking and neurotransmitter release in the synaptic cleft. Published studies highlight a direct link between reduced SNARE complex formation and impairments in neurotransmitter release. While alterations in the SNARE complex have been described following severe focal TBI, it is not known if deficits in SNARE complex formation manifest in a model with reduced severity. We hypothesized that lateral fluid percussion injury (lFPI) reduces the abundance of SNARE proteins, impairs SNARE complex formation and contributes to impaired neurobehavioral function. To this end, rats were subjected to lFPI or sham injury, and tested for acute motor performance and cognitive function at 3 weeks post-injury. lFPI resulted in motor impairment between 1 and 5 days post-injury. Spatial acquisition and spatial memory, as assessed by the Morris water maze, were significantly impaired at 3 weeks after lFPI. To examine the effect of lFPI on synaptic SNARE complex formation in the injured hippocampus, a separate cohort of rats was generated and brains processed to evaluate hippocampal synaptosomal-enriched lysates at 1 week post-injury. lFPI resulted in a significant reduction in multiple monomeric SNARE proteins, including VAMP2, and α-synuclein, and SNARE complex abundance. The findings in the current study are consistent with our previously published observations suggesting that impairments in hippocampal SNARE complex formation may contribute to neurobehavioral dysfunction associated with TBI.